Eucalipto no Rio Grande do Sul : percepção da paisagem e instrumento ecológico do banco de sementes do solo - Abreu, Clarissa Trois (2010)
The eucalyptus plantation is expanding in Rio Grande do Sul, and this fact generated a concern about the environmental impacts from this activity, in special, when implemented in regions where forests are not dominant. It could result in a irreversible change in cultural heritages liked to the ancient landscape, and changes to the ecosystem and grasslands matrix. Assuming that eucalyptus tree plantation imprints new elements on Central Depression landscape. This study propose: analyze the core of the popular resistance against pulp plantations, to figure it out were applied interviews within society sectors (forestry, environmental, general public and small farmers). The Pampa, as a cultural landscape, was cited by the sectors, as the most typical landscape for Rio Grande do Sul. A second approach was proposed to analyze quail and quantitatively the soil seed bank, on four areas with diverse vegetation cover, inside an eucalyptus matrix. With the aim in evaluate the effect of land use in flora behavior. SSB showed a little number of seed at the Native forest at 20 meter from the border 198 seedling m-², followed by eucalyptus 12 years 693 seedlings m-², abandoned area 1470 seedlings m-² and eucalyptus 4 years old 1977 seedling m-². The abandoned area presents Shanon (H = 2,30) and equity (J = 0,71). The Simpson index indicated the highest dominance at eucalyptus 4 years old (0,21), eucalyptus 12 years old and native forest (0,17) and abandoned area (0,13). Were observed border effect and all sites presented a high dominance of herbaceous species from the initial level recover